Video Acara Pinang TV Guna Informasi Pada Kecamatan Pinang Kota Tangerang - Muhamad Sidik; Wahyu Hidayat; Ahmad Bahrul Ulum (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2019)
It's important to access information today, because everyone's information will know it. Pinang Subdistrict is a district in Tangerang city area. Pinang subdistrict is the only service that has Pinang TV. The purpose of this research is to reach the target of the Pinang sub-district in terms of conveying information through the Pinang TV show located in the Tangerang City district to the public. The research methods used in this research include Data collection, Media planning analysis, and Media production concept (KPM) which includes: Pre production, production, and post production. Through the information media Pinang TV Kecamatan Pinang Tangerang City is designed to be informed via: Youtube, Website. The Target is hoped that the district of Pinang is, people can know the awareness that is in the district of Penang that exist in the city of Tangerang, and can increase the number of spectators who see the event Pinang TV.